The Impact of Sleep Quality on Cognitive Functioning in Parkinson's Disease - Stavitsky, Karina; Neargarder, Sandy; Bogdanova, Yelena; McNamara, Patrick; Cronin-Golomb, Alice (Journal of the International Neuropsychological Society, 2012)
In healthy individuals and those with insomnia, poor sleep quality is associated with decrements in performance on tests of cognition, especially executive function. Sleep disturbances and cognitive deficits are both prevalent in Parkinson's disease (PD). Sleep problems occur in over 75% of patients, with sleep fragmentation and decreased sleep efficiency being the most common sleep complaints, but their relation to cognition is unknown. We examined the association between sleep quality and cognition in PD. In 35 non-demented individuals with PD and 18 normal control adults (NC), sleep was measured using 24-hr wrist actigraphy over 7 days. Cognitive domains tested included attention and executive function, memory and psychomotor function. In both groups, poor sleep was associated with worse performance on tests of attention/executive function but not memory or psychomotor function. In the PD group, attention/executive function was predicted by sleep efficiency, whereas memory and psychomotor function were not predicted by sleep quality. Psychomotor and memory function were predicted by motor symptom severity. This study is the first to demonstrate that sleep quality in PD is significantly correlated with cognition and that it differentially impacts attention and executive function, thereby furthering our understanding of the link between sleep and cognition. (JINS, 2012, 18, 108–117)